The diplomatic interpreter's negotiation of power and solidarity through engagement choices: A case study of the Chinese Foreign Minister's 2018 press conference. (March 2021) - Li, Xin; Zhang, Ranran
Abstract: Drawing on the engagement system within appraisal theory (Martin and White, 2005) and the interpreting case of the Chinese Foreign Minister Wang Yi's press conference in March 2018, this article conducts a systematic study of the interpreter's engagement choices compared against the source text engagement profiles. The analysis reveals that while the interpreter re-instantiates the overall power and solidarity relations at the macro-level between the Minister, Chinese journalists and foreign journalists in the target text by largely reproducing the engagement styles of the speakers, he actively intervenes in negotiating power and solidarity through frequent engagement shifts at the micro-level. It is argued that the interpreter's engagement choices are motivated by his ideological alignment with the Chinese government and his institutional power to effectively communicate China's official voices and stances to the world.